Effect of pelleting on survival of porcine epidemic diarrhea virus-contaminated feed - Cochrane, R. A.; Schumacher, L. L.; Dritz, Steven S.; Woodworth, Jason C.; Huss, Anne R.; Stark, Charles R.; DeRouchey, J. M.; Tokach, Michael D.; Goodband, Robert D.; Bai, Jianfa; Chen, Q.; Zhang, J.; et al. (My University, 2017)
Porcine epidemic diarrhea virus (PEDV) is a heat-sensitive virus that has devastated the U.S. swine industry. Because of its heat sensitivity, we hypothesized that a steam conditioner and pellet mill mimicking traditional commercial thermal processing may mitigate PEDV infectivity. Pelleting, a common feed processing method, includes the use of steam and shear forces, resulting in increased temperature of the processed feed. Two thermal processing experiments were designed to determine if different pellet mill conditioner retention times and temperatures would impact PEDV quantity and infectivity by analysis of quantitative reverse transcription PCR and bioassay. In Exp. 1, a 3 x 3 x 2 factorial design was used with 3 pelleting temperatures (68.3, 79.4, and 90.6 degrees C), 3 conditioning times (45, 90, or 180 s), and 2 doses of viral inoculation (low, 1 x 102 tissue culture infectious dose(50) (the concentration used to see cytopathic effect in 50% of the cells)/g, or high, 1 x 10(4) tissue culture infectious dose(50)/g). Noninoculated and PEDV-inoculated unprocessed mash were used as controls. The low-dose PEDV-infected mash had 6.8 +/- 1.8 cycle threshold (Ct) greater (P < 0.05) PEDV than the high-dose mash. Regardless of time or temperature, pelleting reduced (P < 0.05) the quantity of detectable viral PEDV RNA compared with the PEDV-inoculated unprocessed mash. Fecal swabs from pigs inoculated with the PEDV-positive unprocessed mash, regardless of dose, were clinically PEDV positive from 2 to 7 d (end of the trial) after inoculation. However, if either PEDV dose of inoculated feed was pelleted at any of the 9 tested conditioning time x temperature combinations, no PEDV RNA was detected in fecal swabs or cecum content. Based on Exp. 1 results, a second experiment was developed to determine the impact of lower processing temperatures on PEDV quantity and infectivity. In Exp. 2, PEDV-inoculated feed was pelleted at 1 of 5 conditioning temperatures (37.8, 46.1, 54.4, 62.8, and 71.1 degrees C) for 30 s. The 5 increasing processing temperatures led to feed with respective mean Ct values of 32.5, 34.6, 37.0, 36.5, and 36.7, respectively. All samples had detectable PEDV RNA. However, infectivity was detected by bioassay only in pigs from the 37.8 and 46.1 degrees C conditioning temperatures. Experiment 2 results suggest conditioning and pelleting temperatures above 54.4 degrees C could be effective in reducing the quantity and infectivity of PEDV in swine feed. However, additional research is needed to prevent subsequent recontamination after pelleting as it is a point-in-time mitigation step.
Citation: Cochrane, R. A., Schumacher, L. L., Dritz, S. S., Woodworth, J. C., Huss, A. R., Stark, C. R., . . . Jones, C. K. (2017). Effect of pelleting on survival of porcine epidemic diarrhea virus-contaminated feed. Journal of Animal Science, 95(3), 1170-1178. doi:10.2527/jas2016.0961
Keywords: Feed; Pelleting; Porcine Epidemic Diarrhea Virus; Swine; Sufficient; Plasma